THE EVALUATION OF THINKING AND CREATIVELY PROBLEM SOLVING PROJECT OF HUASAI REUNPRACHABAN SCHOOL UNDER THE OFFICE NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 3 - Rodrin, Anchana; Dhammatikul, Akara; Chatakan, Werayut; Promnil, Pramote (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aims 1) to evaluate the system assessment 2) to evaluate the program planning, 3) to evaluate the program implementation 4) to evaluate the program improvement, and 5) to evaluate the program certification to assess program certification (Program Certification) of the evaluation of thinking and creatively problem solving project at Huasai Reunprachaban school under the office Nakhon Si Thammarat primary educational service area office 3. the sample group consists of 1 school administrator, 6 teachers, and 278 students from Kindergarten 1 to Grade 6 at Hua Sai (Ruean Prachaban) School, totaling 285 participants. The evaluation tools for data collection in this evaluation include two questionnaires A questionnaire to assess opinions on the project system and project planning. A questionnaire to assess opinions on program implementation and program acceptance. In addition, an in-depth interview form (In-Depth Interview) was used to assess program improvement, totaling 1 form. and data analysis using percentages, means, and standard deviations The results of the study showed that; Part 1, The evaluation of the project system for developing of creatively problem solving project of Huasai Reunprachaban school showed that, overall, the project was evaluated at the highest level. Part 2, The evaluation of project planning for developing of creatively problem solving project of Huasai Reunprachaban school showed that, overall, the project was evaluated at the highest level. Part 3, The evaluation of program implementation for developing of creatively problem solving project of Huasai Reunprachaban school showed that, overall, the project was evaluated at the highest level. Part 4, The evaluation of program improvement for developing of creatively problem solving project project of Huasai Reunprachaban school showed that, overall, the project was evaluated at the highest level. And Part 5, The evaluation of Acceptance of creatively problem solving project of Huasai Reunprachaban school includes experience-sharing activities and a variety of engaging programs. As a result, students have improved their thinking and analytical processes, leading to increased confidence in expressing themselves and learning how to think systematically. They are also able to apply the skills and knowledge gained to their studies and daily lives.